Tamper-sensitive pre-formed ReRAM-based PUFs: Methods and experimental validation - Wilson, Taylor; Cambou, Bertrand (Frontiers in Nanotechnology, 2022)
In this paper, we present the characterization of pre-formed resistive random access memories to design physical unclonable functions and experimentally validate inherent properties such as tamper sensitivity and a self-destroy mode. The physical unclonable functions were tested for repetitive use, temperature effects, and aging. The variations during successive response generation cycles and drift rates are quantized to explore their reliability. We define tamper-sensitivity as the ability to detect tampering attacks. To establish tamper sensitivity, the cells were characterized for higher current sweeps, and the injected current at which they break down is extracted and analyzed to determine suitable operating ranges. Our experimental results show that at least 91% of the cells can generate keys protected by the scheme, while 20% of the sensing elements are triggered. Finally, the cells were characterized for high Voltage sweeps to be able to destroy the physical unclonable functions on-demand when tampering activity is detected. A fixed Voltage of 1.9 V is enough to destroy the entire array.